Rothavie Toum: capstone - Toum, Rothavie, artist (Colorado State University. Libraries, 2022)
The artist's statement: Good design is the foundation for good communication. All designs obtain a goal to communicate an idea, message, or information. These cannot be translated to a public audience without good design. I outline good design in my use of typography, organization, and inclusive design. These aspects are extremely important ways that I choose to communicate ideas. It allows me to express ideas in visually appealing methods that will resonate with my targeted audience. I always strive to develop meaningful interactions between designs and their audiences. I want viewers to have a positive and long-lasting impression, that draws them back to the client and the designs.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design